BRG1 Mediates Nephronectin Activation in Hepatocytes to Promote T Lymphocyte Infiltration in ConA-Induced Hepatitis - Hong, Wenxuan; Kong, Ming; Qi, Mengwen; Bai, Hui; Fan, Zhiwen; Zhang, Ziyu; Sun, Aijun; Fan, Xiangshan; Xu, Yong (Frontiers in Cell and Developmental Biology, 2021)
Fulminant hepatitis (FH) is a major cause of acute liver failure. Concanavalin A (ConA) belongs to the lectin family and is frequently used as an inducer of FH in animal models. ConA induced FH is characterized by massive accumulation of T lymphocytes in the liver. A host of chemoattractive substances are known to promote T cell homing to the liver during acute hepatitis. Here we investigated the involvement of Brahma-related gene 1 (BRG1), a chromatin remodeling protein, in FH. BRG1-flox mice were crossed to Alb-Cre mice to generate hepatocyte conditional BRG1 knockout (LKO) mice. The mice were peritoneally injected with a single dose of ConA to induce FH. BRG1 deficiency mitigated ConA-induced FH in mice. Consistently, there were fewer T lymphocyte infiltrates in the LKO livers compared to the wild type (WT) livers paralleling downregulation of T cell specific cytokines. Further analysis revealed that BRG1 deficiency repressed the expression of several chemokines critical for T cell homing including nephronectin (Npnt). BRG1 knockdown blocked the induction of Npnt in hepatocytes and attenuated T lymphocyte migration in vitro, which was reversed by the addition of recombinant nephronectin. Mechanistically, BRG1 interacted with β-catenin to directly bind to the Npnt promoter and activate Npnt transcription. Importantly, a positive correlation between infiltration of CD3+ T lymphocyes and nephronectin expression was detected in human acute hepatitis biopsy specimens. In conclusion, our data identify a novel role for BRG1 as a promoter of T lymphocyte trafficking by activating Npnt transcription in hepatocytes. Targeting the BRG1-Npnt axis may yield novel therapeutic solutions for FH.